2015
DOI: 10.1002/cssc.201403057
|View full text |Cite
|
Sign up to set email alerts
|

Tin‐containing Silicates: Alkali Salts Improve Methyl Lactate Yield from Sugars

Abstract: This study focuses on increasing the selectivity to methyl lactate from sugars using stannosilicates as heterogeneous catalyst. All group I ions are found to have a promoting effect on the resulting methyl lactate yield. Besides, the alkali ions can be added both during the preparation of the catalyst or directly to the solvent mixture to achieve the highest reported yield of methyl lactate (ca. 75 %) from sucrose at 170 °C in methanol. The beneficial effect of adding alkali to the reaction media applies not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
140
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 47 publications
8
140
0
1
Order By: Relevance
“…7 Therefore, chemo-catalytic processes attract more and more attentions as a promising alternative to current fermentation procedure. [8][9][10][11][12] In this context, the use of homogeneous Lewis acid catalysts to synthesize LA and MLA was propose. 13 Several compounds as homogeneous catalysts have been found to be efficient for the conversion of biomass to LA, such as Ca(OH) 2 16 and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Therefore, chemo-catalytic processes attract more and more attentions as a promising alternative to current fermentation procedure. [8][9][10][11][12] In this context, the use of homogeneous Lewis acid catalysts to synthesize LA and MLA was propose. 13 Several compounds as homogeneous catalysts have been found to be efficient for the conversion of biomass to LA, such as Ca(OH) 2 16 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the addition of K 2 CO 3 increased the yield of methyl lactate from sucrose at 170 C to 75%. 12 However, the synthesis of Sn-b catalysts are extreme complicate, environmental unfriendly and time consuming. During the process, hydrouoric acid was needed to form hardened gel, and the synthesis took place in autoclave with high pressure for 10 to 20 days to achieve high crystallinity.…”
mentioning
confidence: 99%
“…For the common aldoses and ketoses, these C-C bond-splitting reactions have large activation energies and unfavorable thermodynamics at low-to-moderate temperatures. As a result, most attempts at the catalytic production of C 2 -C 4 α-hydroxy carboxylic acids from hexoses and pentoses have involved high temperatures (≥160°C) (3,9). Carbon basis yields of ∼64-68% of methyl lactate at full conversion were reported for reactions of sucrose catalyzed by Sn-Beta at 160°C for 20 h (3).…”
mentioning
confidence: 99%
“…Recently, methyl lactate yields upwards of 75% from sucrose were achieved with Sn-Beta at 170°C, when specific amounts of alkali carbonates were added to the reaction system (9). Furthermore, the authors suggested that, in the initial study involving Sn-Beta, materials were possibly contaminated by alkali during synthesis, and that alkali-free Sn-Beta recently led to lower yields (30%) (9).…”
mentioning
confidence: 99%
“…Recently, it has been shown that lactic acid esters can be directly obtained from biomass-derived sugars by retroaldol condensation using Lewis acid catalysts. [44][45][46][47] Furfural can also be converted to important dropin chemicals (those usually obtained from petroleum) 50 an precursor for chemical and pharmaceutical industry. 51 Both HMF and furfural can undergo base or acid catalyzed aldol condensation with ketones and aldehydes to yield larger molecules, which can be fully hydrogenated to fuel-range hydrocarbons.…”
Section: 25mentioning
confidence: 99%